Investigation of normal knees kinematics in walking and running at different speeds using a portable motion analysis system - Liu, R.; Qian, D.; Chen, Y.; Zou, J.; Zheng, S.; Bai, B.; Lin, Z.; Zhang, Y.; Chen, Y. (Sports Biomechanics, 2021)
Walking and running at different speeds are common in daily life. This study investigated 6 degrees of freedom (DOF) kinematics of normal knees of Chinese during walking and running. Forty healthy participants were investigated in 4 conditions: comfortable walking, normal walking, slow running and ordinary running. The range of motion (ROM) and peak values in 6 DOF kinematics were analysed. As the speed increased, a general increase in flexion, lateral and proximal translations occurred. Significant increases of ROM in flexion/extension, axial rotation and medial/lateral translations were observed. The ROM of adduction/abduction, anterior/posterior and proximal/distal translations were greatest during normal walking. The maximum and minimum flexion/extension, maximum internal rotation and tibial lateral translations increased with the increase of speed. The maximum and minimum tibial proximal translations in running were found being greater than walking. A phenomenon between walking and running was observed: both tibial proximal/distal and medial/lateral translations increased when changed from walking to running. Non-linear transition exists in 6 DOF kinematics during walking to running. Discoveries in this study may have potential clinical values to serve as references of normal walking and running in the management of knee injury and knee rehabilitation.